2022
DOI: 10.3390/ijms23031043
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Platelets Response during Antiplatelet Treatment after Ischemic Stroke—Between Benefit and Risk: A Systematic Review

Abstract: Ischemic stroke is a disease related to abnormal blood flow that leads to brain dysfunction. The early and late phases of the disease are distinguished. A distinction is made between the early and late stages of the disease, and the best effect in treating an ischemic stroke is usually achieved within the first hours after the onset of symptoms. This review looked at studies platelet activity monitoring studies to determine the risks and benefits of various approaches including antiplatelet therapy. A study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The third limitation may be related to clinical outcome assessment. A number of studies confirmed an increased risk of adverse outcomes in patients with laboratory AR [ 14 , 15 , 16 , 17 ]. However, the underlying mechanism of a poor response to aspirin is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third limitation may be related to clinical outcome assessment. A number of studies confirmed an increased risk of adverse outcomes in patients with laboratory AR [ 14 , 15 , 16 , 17 ]. However, the underlying mechanism of a poor response to aspirin is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Automated (point-of-care) assays such as VerifyNow ® , PFA-100 ® , Multiplate ® , Plateletworks ® and others are widely used for monitoring platelet response to antiplatelet agents including aspirin [ 6 , 12 , 13 ]. HTPR was shown to increase the risk of recurrent vascular events and long-term clinical outcomes for patients with cerebrovascular pathology [ 14 , 15 , 16 , 17 ]. Nevertheless, platelet function tests differ in their ability to predict the risk of cardiovascular outcomes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Routine monitoring of platelet function in all ischemic stroke patients is not recommended, but it is necessary for patients with recurrent ischemic events. 75,76 Increasing evidence showed that the responses to antiplatelet agents are heterogeneous from non-responders to hyper-responders. 77,78 The phenomenon called antiplatelet resistance is associated with the recurrence of ischemic stroke.…”
Section: The Application Of Teg In Aismentioning
confidence: 99%
“…AIS refers to the sudden termination of blood supply to the brain tissue when the cerebral blood flow is below the ischemic threshold (10-25% of baseline) [4], causing irreversible nerve cell damage in the corresponding ischemic area and eventually lead to nerve function impairment. Intracranial atherosclerosis is the most common cause of AIS, and platelets play an inevitable role in subsequent vascular blockage [5].…”
Section: Introductionmentioning
confidence: 99%